Determining Dominant Wind Directions - Selim, S.Z. (2020)
In this paper we address the problem of selecting a ser of wind directions that could represent the wind regime at a location. This problem is cast in the form of a nonconvex mathematical program. Important properties of the problem are discussed and a convergent solution algorithm is designed. The algorithm could yield local optimal solutions. A case study which involves the construction of a transition probability matrix for the wind at a location is presented.